The social aspects of low emission management in the Nowa Sól district = Społeczne aspekty zarządzania niską emisją na terenie powiatu nowosolskiego - Dzikuć, Maciej; Dzikuć, Maria; Siničakova, Marianna (Zielona Góra: Faculty of Economics and Management Press)
The article shows the problem of excessive low emission in the district of Nowa Sól and points to the social issues that can affect a delay in the introduction of specific environmental actions. The article also identifies the main sources that contribute to the formation of low emission in the district of Nowa Sól.
Keywords: niska emisja; ekonomia; ekologia; energia cieplna; low emissions; economy; ecology; heat energy